Comparative and phylogenetic analysis of complete chloroplast genomes from five Artemisia species - Lan, Zhaohui; Shi, Yuhua; Yin, Qinggang; Gao, Ranran; Liu, Chunlian; Wang, Wenting; Tian, Xufang; Liu, Jiawei; Nong, Yiying; Xiang, Li; Wu, Lan (Frontiers in Plant Science, 2022)
Artemisia Linn. is a large genus within the family Asteraceae that includes several important medicinal plants. Most Artemisia species contain terpenoids and flavonoids, which are commonly used in antimalarial, antiinflammatory, hemostatic, and choleretic drugs. Because of their similar morphology and chemical composition, traditional identification methods often fail to distinguish them, which is not conducive for their circulation and drug safety. Therefore, developing an effective identification method for Artemisia species is an urgent requirement. In this study, we analyzed 15 chloroplast (cp) genomes, including 12 newly sequenced genomes, from 5 Artemisia species. We explored their genomic features, codon usage, amino acid frequency, simple sequence repeats (SSRs), and nucleotide diversity analyses. Finally, we constructed a phylogenetic tree comprising 29 cp genomes using maximum likelihood methods. The cp genomes from the five Artemisia species had a typical quadripartite structure and were highly conserved across species. They had varying lengths of 151,132–151,178 bp, and their gene content and codon preferences were similar. A total of 132 genes were annotated, of which 114 were unique and contained 80 protein-coding genes, 30 tRNAs, and 4 rRNAs. We observed 42–50 long repeats and 188–193 SSRs in the cp genomes. Mutation hotspot analysis identified four highly variable regions, which can potentially be used as molecular markers to identify Artemisia species. Phylogenetic analysis showed that the five Artemisia species investigated in this study were sister branches to each other, and individuals of each species formed a monophyletic clade. This study shows that the cp genome can provide distinguishing features to help identify closely related Artemisia species and has the potential to serve as a universal super barcode for plant identification.